Pengaruh Penerapan Praktik Manajemen Sumber Daya Manusia terhadap Keunggulan Kompetitif - Reyhan Mahsa Pratama; Rini Lestari (UNISBA Press, 2021)
Abstract. The phenomenon that occurs in universities in Indonesia shows that there is a lack of competitive advantage so that there are still universities that are closed due to losing in the competition that occurs. This study aims to determine how the implementation of human resource management practices, how to achieve competitive advantage, and how much influence the application of human resource management practices to competitive advantage in A-accredited universities in Bandung City. This research method uses a verification survey with a quantitative approach. This study uses primary data sources obtained through questionnaires filled out by respondents who have positions as heads of departments/departments at A-accredited tertiary institutions in the city of Bandung. The sampling technique used in this study is non-probability sampling, namely purposive sampling technique. Data was collected by distributing online questionnaire links (google form) to respondents. The sample of this study were 15 A-accredited universities in Bandung City and the respondents in this study were 30 leaders in each A-accredited university in Bandung. Hypothesis testing was carried out using a simple regression analysis method using SPSS version 28 software. The results showed that A-accredited universities in Bandung City had the application of human resource management practices with